2018
DOI: 10.1002/biof.1477
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal pre‐receptor cortisol production is inhibited by resveratrol and epigallocatechin gallate through different mechanisms

Abstract: Local activation of cortisol in hormone target tissues is a major determinant of glucocorticoid effect. Disorders in this peripheral cortisol metabolism play an important role in the development of metabolic diseases, such as obesity or type 2 diabetes mellitus. Hence, dietary factors influencing the activity of the involved enzymes can have major impacts on the risk of the above diseases. Resveratrol and epigallocatechin gallate (EGCG), two natural polyphenols found in several nutriments and in green tea, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…RSV was shown to suppress NOX activity, including an O-methylation group, a 4′-OH group, and an extra -OH group. RSV was confirmed to inhibit 11 β -hydroxysteroid dehydrogenase type 1 directly by decreasing cortisol production [95]. With supplementation of anthocyanins, both mRNA and protein level of XOD as well as XOD activity in the serum and liver were inhibited significantly in a dose-dependent manner [64].…”
Section: Antioxidant Effects Of Polyphenols On Metsmentioning
confidence: 99%
“…RSV was shown to suppress NOX activity, including an O-methylation group, a 4′-OH group, and an extra -OH group. RSV was confirmed to inhibit 11 β -hydroxysteroid dehydrogenase type 1 directly by decreasing cortisol production [95]. With supplementation of anthocyanins, both mRNA and protein level of XOD as well as XOD activity in the serum and liver were inhibited significantly in a dose-dependent manner [64].…”
Section: Antioxidant Effects Of Polyphenols On Metsmentioning
confidence: 99%
“…Naringin has been found to suppress metabolic features and improve the number of functional β cells in rats [ 30 , 31 ]. Epigallocatechin gallate (EGCG) could inhibit 11βHSD1 activity and reduce cortisol levels [ 32 , 33 ], improve metabolic features and insulin sensitivity in animals [ 34 ], and renal histology [ 35 , 36 , 37 ]. p -coumaric acid could inhibit insulin resistance and increase adiponectin levels [ 38 , 39 ] Therefore, it is likely that phenolic compounds contained within KH contribute to the inhibition of MetS risk demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With the in‐depth study of RSV, research's shown that RSV has a wide range of pharmacological actions. Such as, anti‐oxidation, 6 anti‐cardiovascular disease, 7 liver protection, 8 anti‐cancer, 9 antibacterial, 10 anti‐inflammatory 11 and anti‐aging. 12 …”
Section: Introductionmentioning
confidence: 99%
“…With the in-depth study of RSV, research's shown that RSV has a wide range of pharmacological actions. Such as, anti-oxidation, 6 anti-cardiovascular disease, 7 liver protection, 8 anti-cancer, 9 antibacterial, 10 anti-inflammatory 11 and anti-aging. 12 Recent studies have pointed out that silent information regulator of transcription 1 (SIRT1) acts as pre-sensor of body energy metabolism, targeting histones, co-regulatory molecules, and metabolic enzymes to regulate gene expression and metabolic activity, thus reflecting the energy state of the cells.…”
mentioning
confidence: 99%